Influência de adjuvantes nas propriedades físico-químicas da calda de inseticidas, na formação de depósitos, penetração cuticular e remoção pela chuva - Melo, Adriano Arrué (2015)
The addition of adjuvants can improve the quality of agricultural chemical sprays and have been an usual practice on the last years. The work presents two papers aiming to study the influence of adjuvant apply on the agricultural spray. The first article, entitled "Influence of adjuvants on the physicochemical characteristics of insecticides spray solution and electron microscope images of the deposits on wheat and corn leaves" evaluate changes in physical and chemical characteristics of the spray solution with the insecticides Thiamethoxam, Imidacloprid and Lambda-cyhalothrin. Were measured the surface tension, droplet contact angle on wheat and maize leaf, droplet coverage and images were made with a scanning electron microscope to better understand the deposit of these insecticides. Adjuvants alter the spray solution physical characteristics improving its wettability, furthermore, the addition of adjuvants may interfere with the deposit characteristics of the tested insecticides. The second article entitled "Tank-mix-adjuvants might improve deposit formation and cuticular penetration, and reduce rain-induced removal of chlorantraniliprole", aimed to verify the interaction of clorantraniliprole insecticide with commercial adjuvants. In this assay, have been studied aspects as adjuvant effect on the deposits formation, cuticular penetration through apple cuticles, droplet coverage and rain effect on the removal of the insecticide in wheat and maize crops. The results showed that the adjuvants play a crucial role in the hydrophobic cover sheet by changing the characteristics of the spray solution, thereby improving the wettability. Furthermore, adjuvants may enhance the absorption of clorantraniliprole insecticide.